Optimization of water and fertilizer management on the intercropping system between maize and mung bean to improve photosynthetic characteristics & water use and to increase plant yield - Gao, Mengfan; Wang, Xinxin; Chen, Renqiang; Gao, Huiyan; Wang, Xiaoling; Liu, Hongquan (Frontiers in Plant Science, 2025)
Intercropping has the advantages of improving the canopy environment and enhancing the productivity of farmland. However, the responses of photosynthetic physiological characteristics, canopy structure and yield to different water and fertilizer measures need to be further clarified. The study took the maize/mung bean intercropping as the cultivation mode, used organic fertilizer instead of chemical fertilizer, combined with the upper and lower limits of field water holding capacity to control the irrigation amount, and set up a two-factor field experiment. The research results show that the leaf area index and chlorophyll relative content of maize and mung beans increase first and then decrease with the emergence time of maize and mung beans. Compared with the treatment without organic fertilizer, the leaf area index of maize and mung beans increased by 5.99% - 36.70% and 27.43% - 28.72% respectively, and the chlorophyll relative content increased by 2.31% - 3.47% and 4.59% - 4.63% respectively. Compared with I0, leaf area index increased by 9.73% - 33.42% and 6.60% - 17.39% respectively, and chlorophyll relative content increased by 2.75% - 12.68% and 4.14% - 9.12% respectively. The gas exchange parameters and absorbance(Ab) of maize and mung beans showed a trend of increasing first and then decreasing with the emergence time. The net photosynthetic rates of maize and mung beans increased by 5.04% - 47.12% and 11.29% - 26.60% respectively. Maize Pn was strongly positively correlated with chlorophyll relative content and Ab (R2>0.5). The three-dimensional growth curves of Pn along with chlorophyll relative content and Ab were S-shaped. As the growth period progressed, the leaves would age, and the gradual decrease of chlorophyll relative content and Ab led to a gradual decrease in maize Pn. Within a certain range, with the increase of irrigation volume, the water use efficiency(WUE) of crops shows a trend of increasing first and then decreasing. Organic fertilizer can significantly improve the WUE of maize/mung beans intercropping crops. In conclusion, optimizing the combination of organic fertilizers and irrigation practices is a win-win strategy that can enhance both grain output and quality.